Frozen section analysis for organ-conserving surgery in penile cancer: Assessing oncological outcomes and trends of local recurrence. (November 2020) - Ellul, T; Grice, P; Mainwaring, A; Bullock, N; Shanahan, A; Cave, D; Dormer, J; Harrison, R; Brown, G; Younis, A; Bose, P; Goddard, JC; et al.
Introduction and objectives: The local recurrence rate of penile cancer following surgical excision is reported in many series to be between 6 and 29%. Intra-operative frozen section (FS) is a useful tool to ensure safe microscopic margins in organ-sparing procedures in penile cancer. In this series, we assessed the rates of positive margins and patterns of local recurrence in a multicentre cohort of patients undergoing penile-preserving surgery assisted by intra-operative FS analysis. Materials and methods: We reviewed all those patients for whom intra-operative FS was employed during penile-preserving surgery in three tertiary referral centres between 2003 and 2016. We assessed whether the use of FS altered the surgical technique and what affect it had on positive margins and recurrence rates. Results: A total of 169 patients were identified. Of these, intra-operative FS examination of the surgical margin was positive in 21 (12%) cases. Final histological examination confirmed cancer-free margins in all but one patient (99.4%). Overall, 9 patients developed local recurrence (5.3%). Conclusions: In this series, intra-operative FS contributed to a very low rate (5.3%) of local recurrence. We noted an extremely low positive margin rate (0.6%) which highlights the benefit of incorporating FS analysis into organ-preserving surgery for penile cancer. Level of evidence: Not applicable for this multicentre audit.